2007
DOI: 10.1128/aem.01238-07
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vibrio cholerae O1 El Tor and O139 Bengal with the Copepods Acartia tonsa and Eurytemora affinis

Abstract: The association of Vibrio cholerae with zooplankton has been suggested as an important factor in transmission of human epidemic cholera, and the ability to colonize zooplankton surfaces may play a role in the temporal variation and predominance of the two different serogroups (V. cholerae O1 El Tor and O139) in the aquatic environment. To date, interactions between specific serogroups and species of plankton remain poorly understood. Laboratory microcosm experiments were carried out to compare quantitatively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 50 publications
1
74
2
1
Order By: Relevance
“…The importance of zooplankton as carrier has been shown for pathogenic bacteria, most notably Vibrio spp. (26). However, the significance of zooplankton association goes beyond pathogenic bacteria, because zooplankton harbors very diverse bacterial phylotypes (19) in great abundances.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of zooplankton as carrier has been shown for pathogenic bacteria, most notably Vibrio spp. (26). However, the significance of zooplankton association goes beyond pathogenic bacteria, because zooplankton harbors very diverse bacterial phylotypes (19) in great abundances.…”
Section: Resultsmentioning
confidence: 99%
“…These regional differences strongly indicate an important effect of the local environment and local zooplankton populations on the dynamics of cholera epidemics. Indeed for Kolkata, higher values of CHL ano reflected the more intense algal blooms than normal that occurred and led to larger zooplankton populations that were comprised mainly of crustacean copepods, a natural aquatic host for V. cholerae (1,8,9). From the analyses of the Dhaka, Bangladesh data, it was concluded that the tidal intrusion of coastal water carrying plankton into inland water could initiate increased human contact with the cholera vibrio (14), because water used for daily hygiene, personal consumption, and religious rites (e.g., ablu- tions) in rural areas of Bangladesh and India is taken directly from local rivers or ponds essentially untreated (13,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…V. cholerae can be found attached to the carapace and in the gut of copepods in large numbers, the copepod essentially serving as a vector for this human pathogen (1,8,9). A single copepod, for example, can contain as many as 10 3 -10 5 V. cholerae cells (10).…”
mentioning
confidence: 99%
“…In aquatic environments, V. cholerae persists by forming biofilms on the surfaces of phytoplankton, zooplankton and chitin debris. 19,20 Biofilms offer a protective environment both against aquatic predators or in the host environment. Overall, the ability to switch between motile and biofilm lifestyles, along with the carefully controlled induction of virulence factors, is central to the establishment of disease and the emergence of cholera epidemics.…”
Section: Resultsmentioning
confidence: 99%